Analisis Yuridis Terhadap Celah Hukum (Loophole) dalam Regulasi Penanaman Modal di Indonesia - Muhammad Andy Prananto; Kamil Rafi Muhammad (JOURNAL SAINS STUDENT RESEARCH, 2026)
This research aims to identify the forms, characteristics, and legal implications of legal loopholes in Indonesia's investment regulations following the enactment of the Job Creation Law. The research method employed is normative legal research using statutory and conceptual approaches. The results indicate that loopholes arise from norm ambiguity, the use of overly general phrasing, and inconsistencies between laws and sectoral implementing regulations. Practices such as nominee agreements and corporate structural engineering serve as tools for business actors to substantively exceed foreign capital limits, even while appearing formally compliant. The existence of these loopholes results in weakened legal certainty and ineffective economic oversight. Therefore, systematic regulatory synchronization between the Investment Law, BKPM regulations, and the risk-based OSS system is required to close these gaps and achieve legal certainty, efficiency, and protection.